Provision of Oligomer Chitosan from Square Rawan Bonds (Squilla mantis) as Effectanti Microba - Agusnar, Harry; Ilyas, Syafruddin (Talenta Publisher, 2022)
We report the provision of chitosan oligomers from pen squid as anti-microbial effect. Chitosan oligomer obtained by adding 10 ml HNO2 in chitosan solution and then incubated for one night at room temperature. Depolymerization of chitosan can be determined by looking at a decrease in its viscosity by using viscometer oswald and molecular weight using the equation Kuhn-Mark-Houwink. Antibacterial test was determined by agar diffusion method. The results showed that the viscosity value of the viscosity standard oligomers with the addition of 10 ml of HNO2 decreased by 76,49% and the molecular weight decreased by 80.94%. Antimicrobial Test uses two microbesstaphylococcus aureus and Escherichia coli with variations in the concentration of 0,5%, 1%, 1.5%, 2% and 2,5% chitosan oligomers, anti-microbial test results obtained the largest clear zone on chitosan oligomers with a concentration of 1% is equal to 13,4 in Escherichia coli and 16,2 in staphylococcus aureus.